PERAN KELOMPOK TANI DAN PENGGUNAAN SARANA PRODUKSI PADA KEGIATAN USAHATANI JAGUNG DI DESA KOMBA-KOMBA KECAMATAN KABANGKA KABUPATEN MUNA - Darmin Darmin; Anas Nikoyan; Hartina Batoa; Darsilan Dima (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
The issues encountered in maize farming activities in Komba-Komba Village can be attributed to several factors. Firstly, the knowledge and expertise of farmers in this area remain limited. Secondly, the role of farmer groups is not yet fully realised. Thirdly, the utilisation of production resources, including seeds, fertilisers and pesticides, is not optimised. The objective of this study was to ascertain the utilisation of production facilities and the function of farmer groups in maize farming activities in Komba-Komba Village, Kabangka Subdistrict, Muna Regency. The research informants were selected purposefully, with specific criteria in mind. Consequently, the research informants totaled 13 individuals, comprising farmer group administrators, specifically two farmer group leaders, two secretaries, two treasurers, six farmer group members, and the village head. Data were collected through observation, in-depth interviews, and document analysis using interview guides. This study focuses on the utilization of production facilities and the role of farmer groups in maize farming. The research employs a qualitative descriptive analysis approach to data analysis, comprising three stages: data reduction, data presentation, and conclusion drawing. The findings indicate that farmer groups in Komba-Komba Village serve as a conduit for collaboration in maize farming activities. This is evidenced by the presence of groups that engage in joint efforts between the farmer group leaders and members during the farming process. Furthermore, the role of farmer groups has not been as effective as the function of farmer groups. In terms of production facilities, farmers in Komba-Komba Village provide these for maize farming activities, including seeds, fertilizers, and pesticides, using their own capital.